Persistent Citation of the Only Published Randomised Controlled Trial of Omega-3 Supplementation in Chronic Obstructive Pulmonary Disease Six Years after Its Retraction - Ashley S. Fulton; Alison M. Coates; Marie T. Williams; Peter R.C. Howe; Alison M. Hill (Publications, 2015)
Scientific articles are retracted infrequently, yet have the potential to influence the scientific literature for years. The only randomised controlled trial to explore the effects of omega-3 polyunsaturated fatty acids in people with chronic obstructive pulmonary disease was retracted in 2008 due to falsified data. The objective of this research was to determine the frequency and nature of citations of this retracted paper. Web of Science and Google Scholar were used to determine the number of times the retracted article was cited. Citations were classified as either “retraction acknowledged” or “retraction not acknowledged”. The search was conducted on 6 August 2013 and updated on 25 March 2014. Results: The search resulted in 76 citations, of which 24 occurred prior to the retraction of the article. Of the 52 citations occurring after the retraction, only two acknowledged the retraction. Of the citations not acknowledging the retraction, 20 referred to specific data and 30 cited the reference in passing. This retracted article continues to be cited by authors, suggesting that information about the retraction was unsuccessfully communicated to the scientific community. Continual citation of retracted literature has the potential to bias a field of research and potentially misinform end-users.